The electrocardiographic, hemodynamic, echocardiographic, and biochemical evaluation of treatment with edaravone on acute cardiac toxicity of aluminum phosphide - Rahimi Kakavandi, Nader; Asadi, Tayebeh; Hooshangi Shayesteh, Mohammad Reza; Baeeri, Maryam; Rahimifard, Mahban; Baghaei, Amir; Noruzi, Marzieh; Sharifzadeh, Mohammad; Abdollahi, Mohammad (Frontiers in Pharmacology, 2022)
Aluminum phosphide (AlP) poisoning can be highly fatal due to its severe toxicity to the heart. Based on the evidence, edaravone (EDA) has protective effects on various pathological conditions of the heart. This research aimed to examine the potential protective effects of EDA on AlP-induced cardiotoxicity in rats. The rats were divided into six groups, including almond oil (control), normal saline, AlP (LD50), and AlP + EDA (20, 30, and 45 mg/kg). Thirty minutes following AlP poisoning, the electrocardiographic (ECG), blood pressure (BP), and heart rate (HR) parameters were examined for 180 min. The EDA was injected 60 min following the AlP poisoning intraperitoneally. Also, 24 h after poisoning, echocardiography was carried out to evaluate the ejection fraction (EF), stroke volume (SV), and cardiac output (CO). The biochemical and molecular parameters, such as the activities of the mitochondrial complexes, reactive oxygen species (ROS), apoptosis and necrosis, and troponin I and lactate levels, were also examined after 12 and 24 h in the heart tissue. According to the results, AlP-induced ECG abnormalities, decrease in blood pressure, heart rate, SV, EF%, and CO were significantly improved with EDA at doses of 30 and 45 mg/kg. Likewise, EDA significantly improved complex I and IV activity, apoptosis and necrosis, ROS, troponin I, and lactate levels following AlP-poisoning (p < 0.05). Also, the mean survival time was increased following EDA treatment, which can be attributed to the EDA’s protective effects against diverse underlying mechanisms of phosphine-induced cardiac toxicity. These findings suggest that EDA, by ameliorating heart function and modulating mitochondrial activity, might relieve AlP-induced cardiotoxicity. Nonetheless, additional investigations are required to examine any potential clinical advantages of EDA in this toxicity.